Plasmid and Host Strain Characteristics of Escherichia coli Resistant to Extended-Spectrum Cephalosporins in the Norwegian Broiler Production. - Solveig Sølverød Mo; Jannice Schau Slettemeås; Einar Sverre Berg; Madelaine Norström; Marianne Sunde (PLoS ONE, 2016)
Escherichia coli resistant to extended-spectrum cephalosporins have been detected in the Norwegian broiler production, despite the fact that antimicrobial agents are rarely used. The genetic mechanism responsible for cephalosporin resistance is mainly attributed to the presence of the blaCMY-2 gene encoding a plasmid-mediated AmpC-beta-lactamase (pAmpC). The aim of this study was to characterize and compare blaCMY-2 containing Escherichia coli isolated from the intestinal flora of broilers and retail chicken meat (fillets) to identify possible successful clones and/or resistance plasmids widespread in the Norwegian broiler production. Methods used included PCR based phylotyping, conjugation experiments, plasmid replicon typing, pulsed-field gel electrophoresis, multiple locus variable-number tandem-repeats analysis and whole genome sequencing. The nucleotide sequence of an IncK plasmid carrying blaCMY-2 was determined. Intestinal isolates displayed a higher degree of genetic diversity than meat isolates. A cluster of genetically related isolates belonging to ST38, phylogroup D, carrying blaCMY-2 containing IncK plasmids was identified. Furthermore, genes encoding plasmid stability systems (relBE/stbDE and pndAC) were identified on the IncK plasmid. Single nucleotide polymorphism (SNP) analysis of a subset of isolates confirmed a close genetic relationship within the two most prevalent STs. The IncK plasmids within these two STs also shared a high degree of similarity. Cephalosporin-resistant E. coli with the same genetic characteristics have been identified in the broiler production in other European countries, and the IncK plasmid characterized in this study showed close homology to a plasmid isolated from retail chicken meat in the Netherlands. The results indicate that both clonal expansion and horizontal transfer of blaCMY-2 containing plasmids contribute to dissemination of cephalosporin resistant E. coli in the broiler production. The presence of plasmid stability systems may explain why the IncK plasmid containing blaCMY-2 is maintained and disseminated in the Norwegian broiler production in absence of selection pressure from the use of antimicrobial agents.